Global Buckling Experiments on Sandwich Columns with Soft Shear Cores - Mario M. Attard (Electronic Journal of Structural Engineering, 2011)
Several failure modes for sandwich columns under compression are said to be possible with shear crimping or shear buckling suggested for short columns with soft shear cores. The buckling formulas and theoretical assumptions of Engesser and Haringx for isotropic columns and soft shear core sandwich columns are reviewed. An important distinction is made between the isotropic column buckling formula attributed to Haringx and the theoretical assumptions underpinning his approach. It is shown that the theoretical approaches of Haringx and Engesser yield the same basic buckling equation for soft shear core sandwich columns when the thickness is very small in comparison to the core thickness, and the shear in the face sheets, the axial force in the core and the bending within the face sheets are ignored. To determine whether shear crimping (shear buckling) is a member or localised type of buckle, tests on low slenderness - short sandwich columns identified as possibly exhibiting shear crimping, were preformed. The test specimens were constructed from 10 mm thick Divinycell H45, H80, H100 and H200 foam for the core and 1 mm face sheets made of Aluminum 2024-T3. The lengths of the columns varied from 20 to 500 mm. The columns were endclamped according to ASTM C 364-99 [1] and placed in a servo-controlled compression testing machine. The width of the specimens was 100 mm and two specimens at each length were tested. The adhesive chosen was a toughened epoxy, trade name “Devcon Epoxy Plus". Measurements of the mid-span lateral displacement were used in a Southwell type plot to determine the elastic global buckling load. The shear modulus of the core was determined from three point bending tests according to ASTM-C-393 [2]. Some of the very short specimens failed with buckling of the face sheet within the clamped region. None of the tests exhibited shear crimpling or shear buckling modes and the global buckling loads for very short columns were much higher than the shear buckling limit of Engesser. Wrinkling failure was not considered.